Avaliação e tratamento da otite externa canina - Mueller, Eduardo Negri (2009)
The goals of this study were to relate cases of ceruminous and purulent external otitis canine in relation to age and breed of the dog, clinical evolution, ear conformation, clinical and microbiological findings; evaluate the effect of topical therapy associated to ceruminolytics in ears with ceruminous external otitis and, evaluate the effect of the ear flushing in ears with purulent external otitis. The ears were evaluated by type of secretion in ceruminous (OC) or purulent (OP). For the treatment of ceruminous external otitis 40 ears were divided in groups A and B, with group A being treated with ceruminolytic and ear solution, and B only with ear solution. For the treatment of purulent otitis 36 ears were divided in groups A1 and B1. The ears of both groups were treated with topical solution and systemic antimicrobial. In group A1 was performed an only ear flushing at day 0.The ears was evaluated clinically (0, 15, 30, 45 days of treatment), and the ears with no pruritus, cerumen/exudate in the acoustic conch and erythema in the clinical otoscopy were discharged. Samples for microbiological evaluation were collected in the three studies. The cases of OC in relation to OP were more frequent in the breed poodle and in the breed brazilian fila, respectivelly, in pendulous ears the evolution of OP was chronic. The average age in OC was 3.3, and in OP, 4.4. The OC were characterized by erythema in the acoustic conch and variable amount of cerumen, and the OP were characterized by the shaking of the head, bad smell, exudate in the acoustic conch, otalgia, ulcers and stenosis and the moderate to intense amount of exudate. In the OC cytology there was predominance of Gram + cocci and yeast, in OP Gram rods and Gram + cocci. In OC the main isolates were M. pachydermatis and S. intermedius. In OP they were Proteus sp., P. aeruginosa and S. intermedius. Amoxicillin associated to clavulanic acid in OC and tobramycin in OP were the antibacterial more effective. In the evaluation of the treatment of OC it was observed that, at day 45, 14 ears of group A and 10 of group B were discharged. However, statistic differences between the treatments in all evaluation were not observed. In the first collection, M. pachydermatis and S. intermedius were isolated, at day 30, none of the samples presented bacterial growth. In the treatment of OP, both groups showed reduced clinical signs at day 45, being discharged 13 ears of group A1 and 12 of group B1. Gram and Gram + were isolated, which decreased in both treatments. Gentamicin was the most effectiveness antibacterial for both studies. It was concluded that, in the conditions studied there was difference in relation to the age, breed, clinical evolution, clinical signs, cytology, isolation and sensibility to antibiotics between ceruminous and purulent otitis; the use of ceruminolytic and ear flushing at day 0, in OC and OP respectively, did not show difference in the reduction of clinical signs, bacterial and fungal isolation and in clinical discharge.